2010
DOI: 10.3389/fnins.2010.00202
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range GABAergic Connections Distributed throughout the Neocortex and their Possible Function

Abstract: Features and functions of long-range GABAergic projection neurons in the developing cerebral cortex have been reported previously, although until now their significance in the adult cerebral cortex has remained uncertain. The septo-hippocampal circuit is one exception – in this system, long-range mature GABAergic projection neurons have been well analyzed and their contribution to the generation of theta-oscillatory behavior in the hippocampus has been documented. To have a clue to the function of the GABAergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 70 publications
6
71
0
Order By: Relevance
“…Previous studies reported the presence of longrange GABAergic projection neurons in the white matter. Most of these cells express nNOS, NPY, and somatostatin (Tomioka et al, 2005;Higo et al, 2007Higo et al, , 2009Tomioka and Rockland, 2007;Tamamaki and Tomioka, 2010) and are not identical with the cell population characterized in this study. Interestingly, some EGFP-positive WMICs have dendrites in the striatum and hippocampus and axons reaching into the cortex.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies reported the presence of longrange GABAergic projection neurons in the white matter. Most of these cells express nNOS, NPY, and somatostatin (Tomioka et al, 2005;Higo et al, 2007Higo et al, , 2009Tomioka and Rockland, 2007;Tamamaki and Tomioka, 2010) and are not identical with the cell population characterized in this study. Interestingly, some EGFP-positive WMICs have dendrites in the striatum and hippocampus and axons reaching into the cortex.…”
Section: Discussionmentioning
confidence: 87%
“…Subplate neurons are probable candidates for hub neurons in the developing cortex given that this transient cortical region was recently identified as a 'hub station' [103]. In addition, hippocampal hub cells share several remarkable properties with subsets of subplate neurons, including long distance projections and the ability to drive synchronization in the developing cortical plate [103][104][105].…”
Section: Statistical Relationshipmentioning
confidence: 99%
“…We used positive correlation to examine areas that are co-activated. It may also be possible to examine areas that are negatively correlated where one region may inhibit another 45 .…”
Section: Relation Of Activity Propagation To Axonal Projectionsmentioning
confidence: 99%
“…However, most inhibitory projections do not span long distances 45 . More detailed analysis of cortical activity 46 will likely reveal cortical layer specific functional connections that may be influenced by local intracortical inhibition.…”
Section: Relation Of Activity Propagation To Axonal Projectionsmentioning
confidence: 99%